math

posted by .

Find the derivative of the function and evaluate
f '(x)
at the given value of x.
f(x) = 4x + 5/4x − 5 ; x = 4

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math

    i need to find when the function increases or decreases, this is the derivative of the function (10 − 3x)/(2 ¡î5 − x) but how do you solve the function when x is zero?
  2. Math

    First, give the technology formula for the given function and then use technology to evaluate the function for the given values of x. (Round your answers to four decimal places.) r(x) = 4x2 + 1/4x2 − 1; x = −1, 0, 1, ..., …
  3. CALCULUS HELP

    Find the second derivative for the function 5x^3+60x^2-36x-41 and solve the equation F(X)=0 i got to the second derivative but what do we do next to be able to get one of these answers.. F(x) = 5x3+60x2−36x−41 1. derivative …
  4. Math

    Find the derivative of the given function. f(x)=(ãx+9x)(x^3/2-x) f '(x) = ?
  5. Pre-Calculus

    Determine the derivative at the point (2,−43) on the curve given by f(x)=7−7x−9x^2. I know that the answer is -43, but I was wondering if it was just a coincidence that the derivative at the point (2,−43) is …
  6. Last two CALC questions. :)

    8. If f(x) = sin(7 − 5x), find f′(π), which is the derivative at π: −0.754 −0.657 0 * 0.657 3.770 9. Given the function: g(x)={x+b, x<0 {cos(x), x≥0 Find the value of b, if any, that will …
  7. Calculus

    Given f(x)=−2x^3 -3x + 1, the value of the derivative of the inverse function, f^−1(x) at x=−21 is (f^1)′(−21)= ?
  8. Alg

    Given f(x) = 2x^2 – 2 and g(x) = –2x + 4, find the following. (f − g)(2) AND Given f(x) = 2x − 2 and g(x) = 4x − 5, evaluate the composite function. f[g(2)]
  9. Calculus

    Find the first partial derivatives and evaluate each at the given point. Function w = 2x^2y − 6xyz + 10yz^2 Point (2, 5, −3) wx(2, 5, −3) = wy(2, 5, −3) = wz(2, 5, −3) =
  10. Calculus

    Find the first partial derivatives and evaluate each at the given point. Function w = sqrt(5x^2 + y^2 − 4z^2) Point (2, −4, 2) wx(2, −4, 2) = wy(2, −4, 2) = wz(2, −4, 2) =

More Similar Questions